Rheumatoid knee synovitis successfully treated with intra-articular rifamycin SV. Issue 3 (June 1982) - Caruso, I; Montrone, F; Fumagalli, M; Patrono, C; Santandrea, S; Gandini, M C
Abstract : Thirty rheumatoid patients with persistent knee effusion were treated intra-articularly with rifamycin SV, 500 mg weekly, or with saline solution, 10 ml, in a double-blind study. A complete disappearance of effusion and an impressive clinical improvement was observed in the patients on rifamycin. The synovial fluid and membrane underwent some changes. In 2 patients the rifamycin caused a painful local reaction. After a follow-up of 5 years only one patient has experienced effusion relapse, 5 months after the termination of rifamycin SV treatment. The patients on saline showed no significant change. On the basis of the results obtained from the monoarthritis experimental model and from clinical trials it is tempting to consider that rifamycin has an antimitotic effect, impeding the synthesis of RNA and DNA polymerases in immunocompetent cells.